7th LICMAS 2022 Book of Abstracts: 7th Libyan International Conference on Medical, Applied, and Social Sciences - Atia, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2023)
This is a collection of abstracts that was submitted to be particpated in the 7th Libyan International Conference on Medical, Applied, and Social Sciences 2023 held by the University of Tripoli Alahlia between the period of 1-3 June 2023